Pelayanan Pastoral bagi Jemaat yang Sulit di Gereja - Agung Gunawan (Cipanas Theological Seminary, 2021)
ABSTRACTABSTRACTThis article will discuss how to deal with difficult people in the church. Church leaders should not antagonize or even remove them from the church. Difficult people in the church should not be avoided but must be dealt with properly and correctly.In dealing with them the church leaders did not contradict them. Church leaders have a duty to provide pastoral care for them. In this article, we will first discuss the types of difficult people in the church. Next will be described the ministry of important principles in pastoral care needed by difficult people in the church. The hypothesis of this article is that through appropriate pastoral care, difficult people in the church can be transformed into good individuals and support church ministry.Keyword:. Pastoral Care, difficult people, in the church